2008
DOI: 10.1038/nature06896
|View full text |Cite
|
Sign up to set email alerts
|

A massive binary black-hole system in OJ 287 and a test of general relativity

Abstract: Tests of Einstein's general theory of relativity have mostly been carried out in weak gravitational fields where the space-time curvature effects are first-order deviations from Newton's theory. Binary pulsars provide a means of probing the strong gravitational field around a neutron star, but strong-field effects may be best tested in systems containing black holes. Here we report such a test in a close binary system of two candidate black holes in the quasar OJ 287. This quasar shows quasi-periodic optical o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
342
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(360 citation statements)
references
References 23 publications
14
342
0
4
Order By: Relevance
“…The observed light curve of Sharov 21 is roughly fitted by either of the two scenarios, but more detailed modelling is necessary to decide if the flare can be reproduced accurately. Finally, we cannot exclude that the flare is part of a quasi-periodic activity similar to OJ 287 (Valtonen et al 2008) on an intrinsic time scale of > ∼ 10 yr. The remarkable quasar Sharov 21 obviously merits further efforts, both for the completion of the light curve and for its modelling.…”
Section: Discussionmentioning
confidence: 99%
“…The observed light curve of Sharov 21 is roughly fitted by either of the two scenarios, but more detailed modelling is necessary to decide if the flare can be reproduced accurately. Finally, we cannot exclude that the flare is part of a quasi-periodic activity similar to OJ 287 (Valtonen et al 2008) on an intrinsic time scale of > ∼ 10 yr. The remarkable quasar Sharov 21 obviously merits further efforts, both for the completion of the light curve and for its modelling.…”
Section: Discussionmentioning
confidence: 99%
“…A simple estimate of the fraction of quasars that would harbour binaries with an orbital period t bin can be obtained from the residence time tres = a/ȧ at each separation a, and the lifetime of bright (LQ/L edd ∼ > 1 Note that in the precessing binary model for OJ287 (Lehto & Valtonen 1996;Valtonen et al 2008), the orbital period is 12.2 yr, the primary is very massive (∼ 1.8×10 10 M ), but the secondary is light (∼ 1.4×10 8 M ). The latter reduces the efficiency of GWs, but increases the impact of a gas disc; as a result, the OJ287 binary is gas-driven, well before decoupling.…”
Section: Binary Fraction Among Quasarsmentioning
confidence: 99%
“…OJ 287 shows a periodical behaviour in its optical emission. Analysing its historical light-curve, several studies concluded that it shows a period of ∼12 years (Sillanpaa et al 1988(Sillanpaa et al , 1996, explained by a binary black hole system (Sillanpaa et al 1988;Valtaoja et al 2000;Valtonen et al 2008). Variability has also been detected both at radio and X-ray wavelengths Hughes et al 1998;Hovatta et al 2008).…”
Section: Resultsmentioning
confidence: 99%